PENGARUH PELATIHAN TERHADAP KINERJA KARYAWAN BANK PEMBIAYAAN RAKYAT SYARIAH BHAKTI SUMEKAR SUMENEP - cici' insyiah (Assyarikah: Journal of Islamic Economic Business, 2020)
Sharia banking is now starting to become a solution, no longer just an alternative to financial problems, as evidenced by the 1998 monetary crisis, Islamic banking remained strong. This is of course supported by the existence of management elements that have been managed well by Islamic banking. The existence of employee performance that continues to increase, and training is part of these management elements, so that the positive stigma of Islamic banking can be endemic to the wider community. The purpose of this study was to determine the effect and magnitude of the effect of training on the performance of employees of BPRS Bhakti Sumekar Sumenep. This study uses a quantitative approach with a simple linear regression analysis technique. The results of the study indicate that there is an effect of training on the performance of employees of BPRS Bhakti Sumekar Sumenep. Based on the results of the coefficient of determination (R2) using SPSS version 18, with the acquisition of R square of 0.129. This means that 12.9% of employee performance is explained through training for employees of BPRS Bhakti Sumekar Sumenep. While the remaining 87.1% can be explained by other factors. From the results of this study, this is caused by, First: The training program cannot be transferred in daily tasks. because the method used in the company is different, this happens because sometimes the training material provided is about conventional banks while this is not in accordance with the BPRS Bhkti Sumekar Sumenep. Second: There is no follow-up regarding the results of the training. The absence of evaluation after the implementation of the training resulted in the ineffectiveness of the results of the training itself, because there was no serious follow-up regarding training in the world of work. This is where the manager's job as a leader must be keen to see and analyze the training program. So that the training provided to employees will be beneficial for employees.